Contribution of type 2 diabetes to major adverse cardiovascular events (MACE) in a long-term observational study with different stages of atherosclerosis - Arthur Mader; Dario Haeberli; Barbara Larcher; Jörn F. Dopheide; Christoph H. Saely; Christine F. Heinzle; Peter Amann; Marc Schindewolf; Andreas Festa; Heinz Drexel (Scientific Reports)
Abstract The impact of diabetes on incident cardiovascular disease in relation to the extent of atherosclerotic disease remains unclear. We aimed to investigate major adverse cardiovascular events (MACE) in patients with or without type 2 diabetes (T2DM) presenting with two extremes of atherosclerotic disease, those with angiographically documented minor coronary atherosclerotic lesions and those with symptomatic peripheral artery disease. We included 1238 patients from two prospective, long-term cohort studies. Patients underwent coronary angiography and/or sonography in order to assess the grade of atherosclerosis and were defined as having no signs of Atherosclerosis (n = 332; Group I), minor atherosclerosis (n = 425; Group II) and major atherosclerosis (n = 481; Group III). Cardiovascular events were recorded over a median follow-up period of 7.1 years (Q1 = 3.6 years, Q2 = 7.1 years, Q3 = 11.3 years), covering a total of 9533 patient years. We tested the hypothesis that T2DM infers the same relative risk increase irrespective of the atherosclerosis stage, considering 3-point MACE as the primary endpoint. Incident MACE was reported in 681 patients (51%). MACE occurred more frequently in patients with T2DM than in patients without T2DM (p < 0.001). Further, MACE occurred more frequently in group III (58.1%), than group II (34.1%) or group I (19.1%) (group I vs. group II vs. group III, p < 0.001). In a cox-regression-model, T2DM was a significant predictor of MACE in univariate analyses (HR = 2.43 [1.88–3.14], p < 0.001) and after multivariate adjustment for cardiovascular risk factors, as well as the different grades of atherosclerosis (HR = 1.37 [1.02–1.84], p = 0.034). Also, atherosclerosis grades predicted MACE (HR = 3.19 [2.75–3.70], p < 0.001) in univariate analyses, and also after multivariate adjustment for known cardiovascular risk factors, including T2DM (HR = 1.61 [1.31–1.98], p < 0.001). Finally, when testing for interactions between T2DM and stages of atherosclerosis on MACE we could not find any significant interaction (HR = 1.14 [0.86–1.52], p = 0.364). We conclude that T2DM infers an increased risk for MACE across anatomically and morphologically distinct stages of atherosclerosis.